Professional Education in Higher Educational Institutions: A study on Knowledge Management through E-Governance Model - Jindal, Gaurav; Kumawat, Chandikaditya; Tyagi, Jaikishore (International Journal of Computer Sciences and Engineering, 2019)
In recent times, higher education is not favourable time period. Various challenges and pressures are associated with it. Professional Education requires collaborative use of workers, employees in an organization or company. The key professionals involved in knowledge management programs are information technologists and human resource manager including information professionals. So, there is great need to maintain indulgence and adoption of latest standards in field of professional education so as to gain global leadership positions. In simple words, Knowledge Management (KM) is task of developing, sharing and analyzing knowledge obtained through individual’s experience within organization. The following paper revolves around the conceptual framework in lieu of Knowledge Management (KM) practices in various B-Schools and universities in Delhi like Jamia Milia, GGSIPU, Delhi University, JNU etc. In this paper, e-governance model and its application on professional education has also been presented. E-governance is best approach for bringing transformation to employees’ lives. It may lead to interaction of organization in process of education plan and management of institutions.